The effect of upper-body positioning on the aerodynamic-physiological economy of time-trial cycling - Faulkner, S. H.; Jobling, P. (International Journal of Sports Physiology and Performance, 2021)
Purpose: Cycling time trials (TTs) are characterized by riders` adopting aerodynamic positions to lessen the impact of aerodynamic drag on velocity. The optimal performance requirements for TTs likely exist on a continuum of rider aerodynamics versus physiological optimization, yet there is little empirical evidence to inform riders and coaches. The aim of the present study was to investigate the relationship between aerodynamic optimization, energy expenditure, heat production, and performance. Methods: Eleven trained cyclists completed 5 submaximal exercise tests followed by a TT. Trials were completed at hip angles of 12° (more horizontal), 16°, 20°, 24° (more vertical), and their self-selected control position. Results: The largest decrease in power output at anaerobic threshold compared with control occurred at 12° (-16 [20] W, P = .03; effect size [ES] = 0.8). There was a linear relationship between upper-body position and heat production (R2 = .414, P = .04) but no change in mean body temperature, suggesting that, as upper-body position and hip angle increase, convective and evaporative cooling also rise. The highest aerodynamic-physiological economy occurred at 12° (384 [53] W·CdA/L·min, ES = 0.4), and the lowest occurred at 24° (338 [28] W·CdA/L·min, ES = 0.7), versus control (367 [41] W·CdA/L·min). Conclusion: These data suggest that the physiological cost of reducing hip angle is outweighed by the aerodynamic benefit and that riders should favor aerodynamic optimization for shorter TT events. The impact on thermoregulation and performance in the field requires further investigation.